Social Security as Trade among Living Generations - Hansson, Ingemar; Stuart, Charles (American Economic Review, 1989)
We study Social Security legislated endogenously by altruistic, overlapping generations. Starting from a steady-state equilibrium without Social Security, both generations living in a period can gain from legislation that mandates transfers from young to old in that and all subsequent periods. The Social Security allocation is Pareto-optimal. Later living pairs of generations may lose, but do not amend the law.